Odd Vs. Even: The Case of Arbitral Tribunals - Al-Hawamdeh, Ahmed; Ababneh, Alaeldin (DIRASAT: SHARI’A AND LAW SCIENCES, 2018)
The aim of this paper is to focus on the accepted number of arbitrators in law and practice. It is common practice for arbitration agreements to address the number of the arbitrators. Selecting the number of arbitrators is one of the most critical issues in arbitration and it is vitally important to the effectiveness and speed of the arbitration process. Indeed, arbitration clauses often specify the number of persons who will comprise the tribunal in the event of future disputes. However, if the parties do not agree upon the number of arbitrators, institutional rules usually grant the institution power to do so. On the other hand and in the case of ad hoc arbitration, national courts will have the power to decide on the default number rules in based on the arbitration legislation. This paper points out that although the sole or odd number for an arbitral tribunal is commonly used to the extent that it seems to be the only accepted rule, the even number is also accepted under certain trades, rules and legislation, nationally and internationally. Many questions arise from applying the odd number in arbitration, which this paper aims to answer. Moreover, there are some conditions that need to be met in the case of choosing an even number. This paper highlights the underpinning arguments behind both the odd and even number rules in arbitration, evaluating the advantages and disadvantages of each case.